Preparation method of wear-resistant rubber composite material

By introducing trifluoromethyldiamine monomer and 4,4'-diphenylene dianhydride into the polyimide and undergoing thiol-ene click reaction with polyisoprene to form polyisoprene grafted polyimide, the problem of poor wear resistance and heat aging resistance of natural rubber is solved, and the mechanical properties and wear resistance of rubber materials are significantly improved.

CN119505383APending Publication Date: 2025-02-25ZIBO HUAQING REFRACTORIES
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411687692.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-25
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

Natural rubber has poor wear resistance, poor mechanical strength and heat-resistant aging performance.

Method used

By introducing trifluoromethyldiamine monomer and 4,4'-diphenylether dianhydride into the polyimide for amidation reaction, a soluble alkenyl polyimide was obtained, and thiol-ene click reaction was carried out with polyisoprene to form polyisoprene grafted polyimide, and then mixed and vulcanized with natural rubber, zinc oxide, stearic acid and other materials to prepare a wear-resistant rubber composite material.

Benefits of technology

It significantly improves the tear strength and Shore A hardness of the rubber material, reduces the acron wear, improves the mechanical properties and wear resistance of natural rubber, and enhances its heat resistance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_4
    Figure SMS_4
  • Figure QLYQS_1
    Figure QLYQS_1
Patent Text Reader

Abstract

The invention relates to the technical field of natural rubber, and discloses a preparation method of a wear-resistant rubber composite material, which comprises the following steps: adding natural rubber, polyisoprene grafted polyimide, zinc oxide, an accelerant, an anti-aging agent, vulcanizing and the like into a double-roller open mill, mixing, and vulcanizing in a press vulcanizer to obtain the wear-resistant rubber composite material. A large number of polyisoprene molecular chains are introduced into side chains of polyimide, so that the compatibility between polyimide and natural rubber is improved, polyimide is uniformly dispersed in a natural rubber matrix, a very good reinforcing effect is achieved, the tearing strength and the Shore A hardness of a rubber material are improved, the Akron abrasion loss is reduced, and the service life of the rubber material is prolonged. The mechanical property, the wear resistance and the heat resistance of the natural rubber material are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of natural rubber, in particular to a method for preparing a wear-resistant rubber composite material. Background Art

[0002] Natural rubber is a natural polymer compound with polyisoprene as the main component. It has good resilience, insulation, water resistance, plasticity and processing properties, and is widely used in various fields of industrial production and daily life. However, natural rubber has poor wear resistance, mechanical strength and heat aging resistance. Reinforcement and modification of natural rubber is a research hotspot. Polyisoprene contains unsaturated double bonds, which can undergo epoxidation, thiol click reactions, etc., which expands the practical application of polyisoprene.

[0003] Polyimide is a high-performance synthetic resin material with high mechanical strength, high modulus, good high temperature resistance and excellent wear resistance. Introducing trifluoromethyl and other groups into the molecular chain of polyimide can give it good solubility in organic solvents. Compounding polyimide with polymer materials such as nitrile rubber, natural rubber, epoxy resin, phenolic resin, etc. can improve the strength, wear resistance, heat resistance, flame retardancy and other properties of the material. Chinese patent CN104231348B discloses melt extrusion of polyimide fibers such as natural rubber, damping agent, antioxidant, etc., and the obtained rubber composite material has good mechanical properties and damping properties. However, this patent does not improve the wear resistance and heat aging resistance of natural rubber. Summary of the invention

[0004] The invention solves the problem that the natural rubber has poor mechanical properties and wear resistance.

[0005] The technical solution is: a method for preparing a wear-resistant rubber composite material:

[0006] Step S1, adding trifluoromethyldiamine monomer and 4,4'-biphenyl ether dianhydride in a molar ratio of 100:(90-110) to N,N-dimethylformamide, stirring and reacting at 20-30°C for 6-10h, then pouring the solution into a mold, placing it in an oven for thermal imidization, the process is sequentially kept at 150-160°C for 1.5-2h, kept at 200-210°C for 2-3h, kept at 240-250°C for 1.5-2h, kept at 280-300°C for 1-1.5h, cooled, and obtained a soluble olefin polyimide.

[0007] Step S2, add soluble alkenyl polyimide to N,N-dimethylformamide, stir and dissolve, then add polyisoprene, toluene cosolvent, azobisisobutyronitrile and mercapto crosslinking agent, heat to 65-80°C, stir and react for 48-72h, pour the solution into methanol, filter and wash with ethanol to obtain polyisoprene grafted polyimide.

[0008] Step S3, adding 100 parts by weight of natural rubber, 5-30 parts of polyisoprene grafted polyimide, 4-5 parts of zinc oxide, 3.4-4.2 parts of stearic acid, 2-2.6 parts of accelerator, and 1.3-1.6 parts of antioxidant into a double-roll open mill, mixing for 4-6 minutes, and then adding 1.4-1.8 parts of sulfur. After mixing, the obtained mixed rubber is vulcanized in a flat vulcanizer at 145-150° C. for 20-30 minutes, and the material is discharged to obtain a wear-resistant rubber composite material.

[0009] Preferably, in step S2, the mass ratio of the soluble olefin polyimide, polyisoprene, azobisisobutyronitrile, and mercapto crosslinking agent is 100:(8-20):(0.04-0.1):(0.3-0.8).

[0010] Preferably, the mercapto crosslinking agent is pentaerythritol tetrakis-3-mercaptopropionate or trimethylolpropane tris(thioglycolic acid).

[0011] Preferably, in step S3, the accelerator is any one or a combination of tetramethylthiuram disulfide, 2,2'-dibenzothiazole disulfide, and N-cyclohexyl-2-benzothiazole sulfenamide; and the antioxidant is N-cyclohexyl-N'-phenyl-p-phenylenediamine.

[0012] Preferably, the preparation method of trifluoromethyldiamine monomer is:

[0013] (1) Add 3-nitro-5-(trifluoromethyl)benzoic acid, 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride, and 1-hydroxybenzotriazole to N,N-dimethylformamide and stir to activate for 60-90 minutes. Then add 4,4'-diaminobenzene dihydrochloride and potassium carbonate and stir to react for 12-18 hours. Add saturated sodium bicarbonate solution, filter, wash with water, and separate by silica gel column chromatography to obtain an intermediate.

[0014] (2) Add the intermediate, Pd / C catalyst and hydrazine hydrate solution in a mass ratio of 100:(4.4-5.2):(60-74) to ethanol, heat to 70-80°C, condense and reflux for 18-24 hours, filter and rotary evaporate the filtrate, separate by silica gel column chromatography, and obtain trifluoromethyldiamine monomer.

[0015] Preferably, the molar ratio of 3-nitro-5-(trifluoromethyl)benzoic acid, 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride, 1-hydroxybenzotriazole, 4,4'-diaminostilbene dihydrochloride, and potassium carbonate is (200-220):(210-230):(210-230):100:(340-380).

[0016] The beneficial effect is that: the present invention uses 3-nitro-5-(trifluoromethyl)benzoic acid and 4,4'-diaminobenzene dihydrochloride as reactants, undergoes amidation reaction and reduction reaction, obtains trifluoromethyl diamine monomer containing alkenyl, and then undergoes polymerization reaction with 4,4'-biphenyl ether dianhydride to obtain fluorine-containing alkenyl polyimide. Thus, a large amount of trifluoromethyl is introduced into the side chain of the polyimide, which improves the solubility of the polyimide, and has good solubility in solvents such as N,N-dimethylformamide.

[0017] The main chain of the soluble alkenyl polyimide of the invention contains alkenyl groups. Pentaerythritol tetrakis-3-mercaptopropionate and the like are used as a mercapto crosslinking agent. Under the initiation of azobisisobutyronitrile, a plurality of mercapto groups of the crosslinking agent respectively undergo mercapto-ene click reactions with alkenyl groups of the polyimide and alkenyl groups of polyisoprene, thereby introducing a large number of polyisoprene molecular chains into the side chains of the polyimide, significantly improving the compatibility between the polyimide and natural rubber, making the polyimide uniformly dispersed in a natural rubber matrix, playing a good reinforcing role, improving the tear strength and Shore A hardness of the rubber material, reducing the Akron abrasion loss, and improving the mechanical properties and wear resistance of the natural rubber material.

[0018] Polyimide itself has strong high temperature resistance. At the same time, the soluble olefin polyimide is evenly dispersed in the natural rubber matrix, which is beneficial to improve the heat resistance of natural rubber. After heat aging tests, the rubber material still has low Akron abrasion and high tear strength and Shore A hardness, maintaining good wear resistance and mechanical properties. DETAILED DESCRIPTION

[0019] The principles and features of the present invention are described below in conjunction with specific embodiments. The examples are only used to explain the present invention and are not used to limit the scope of the present invention. The methods used in the present invention are all conventional methods unless otherwise specified, and the drugs used in the present invention are all commercially available products.

[0020] Example 1: (1) Add 40 mmol 3-nitro-5-(trifluoromethyl)benzoic acid (CAS No. 328-80-3), 42 mmol 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride (EDCl), and 42 mmol 1-hydroxybenzotriazole (HOBt) to 500 mL N,N-dimethylformamide, stir and activate for 60 min, then add 20 mmol 4,4'-diaminobenzene dihydrochloride (CAS No. 54760-75-7) and 76 mmol potassium carbonate, stir and react for 18 h, add saturated sodium bicarbonate solution, filter and wash with water, separate by silica gel column chromatography, and the eluent is a mixed solution of petroleum ether and ethyl acetate to obtain an intermediate. Yield 7.12 g.

[0021] (2) Add 5 g of the intermediate, 0.22 g of Pd / C catalyst, and 3.9 g of hydrazine hydrate solution to 80 mL of ethanol, heat to 80 ° C, condense and reflux for 24 hours, filter, rotary evaporate the filtrate, separate by silica gel column chromatography, and use a mixed solution of petroleum ether and ethyl acetate as the eluent to obtain trifluoromethyldiamine monomer. The yield is 3.42 g. The preparation reaction formula is as follows:

[0022] .

[0023] Example 2: (1) Add 44 mmol 3-nitro-5-(trifluoromethyl)benzoic acid, 46 mmol 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride, and 46 mmol 1-hydroxybenzotriazole to 600 mL N,N-dimethylformamide, stir and activate for 90 min, then add 20 mmol 4,4'-diaminobenzene dihydrochloride and 68 mmol potassium carbonate, stir and react for 12 h, add saturated sodium bicarbonate solution, filter and wash with water, separate by silica gel column chromatography, and the eluent is a mixed solution of petroleum ether and ethyl acetate to obtain an intermediate. Yield 7.35 g.

[0024] (2) Add 5 g of the intermediate, 0.26 mg of Pd / C catalyst, and 3 g of hydrazine hydrate solution to 60 mL of ethanol, heat to 70 ° C, condense and reflux for 18 h, filter, rotary evaporate the filtrate, separate by silica gel column chromatography, and use a mixed solution of petroleum ether and ethyl acetate as the eluent to obtain trifluoromethyldiamine monomer. The yield is 3.57 g.

[0025] Example 3: Step S1, add 10mmol trifluoromethyldiamine monomer (prepared in Example 1) and 10mmol 4,4'-biphenyl ether dianhydride to N,N-dimethylformamide, stir and react at 25°C for 10h, then pour the solution into a mold and place it in an oven for thermal imidization, the process is sequentially kept at 150°C for 2h, 200°C for 3h, 240°C for 1.5h, 300°C for 1h, and cooled to obtain a soluble olefin polyimide. The preparation reaction formula is as follows:

[0026] .

[0027] Step S2, add 30g of soluble alkenyl polyimide to 800mL N,N-dimethylformamide, stir and dissolve, then add 3.9g of polyisoprene, 100mL of toluene cosolvent, 17mg of azobisisobutyronitrile and 130mg of pentaerythritol tetra-3-mercaptopropionate, heat to 65°C, stir and react for 72h, pour the solution into methanol, filter and wash with ethanol to obtain polyisoprene grafted polyimide. The preparation reaction formula is:

[0028] .

[0029] Step S3, adding 10kg natural rubber, 500g polyisoprene grafted polyimide, 400g zinc oxide, 360g stearic acid, 54g accelerator tetramethylthiuram disulfide and 146g N-cyclohexyl-2-benzothiazole sulfonamide, 130g antioxidant N-cyclohexyl-N'-phenyl-p-phenylenediamine into a double-roll mill, mixing for 4min, then adding 180g sulfur, and after mixing, vulcanizing the obtained mixed rubber in a flat vulcanizer at 145°C for 30min, discharging, and obtaining a wear-resistant rubber composite material.

[0030] Example 4: Step S1, add 10mmol trifluoromethyldiamine monomer (prepared by Example 1) and 11mmol 4,4'-biphenyl ether dianhydride to N,N-dimethylformamide, stir and react at 20°C for 10h, then pour the solution into a mold, and place it in an oven for thermal imidization. The process is to keep it at 150°C for 2h, 200°C for 3h, 250°C for 1.5h, and 280°C for 1h, cool it, and obtain a soluble olefin polyimide.

[0031] Step S2, add 30g of soluble alkenyl polyimide to 800mL of N,N-dimethylformamide, stir to dissolve, add 6g of polyisoprene, 150mL of toluene cosolvent, 130mg of azobisisobutyronitrile and 240mg of pentaerythritol tetrakis-3-mercaptopropionate, heat to 70°C, stir to react for 72h, pour the solution into methanol, filter and wash with ethanol to obtain polyisoprene grafted polyimide.

[0032] Step S3, adding 10kg natural rubber, 1kg polyisoprene grafted polyimide, 450g zinc oxide, 420g stearic acid, 62g accelerator tetramethylthiuram disulfide and 154g 2,2'-dibenzothiazole disulfide, 160g antioxidant N-cyclohexyl-N'-phenyl-p-phenylenediamine into a double-roll mill, mixing for 6min, then adding 170g sulfur, and after mixing, vulcanizing the obtained mixed rubber in a flat vulcanizer at 150°C for 20min, discharging, and obtaining a wear-resistant rubber composite material.

[0033] Example 5: Step S1, add 10 mmol trifluoromethyldiamine monomer (prepared by Example 1) and 10 mmol 4,4'-biphenyl ether dianhydride to N,N-dimethylformamide, stir and react at 30°C for 6 hours, then pour the solution into a mold, and place it in an oven for thermal imidization. The process is to keep it at 160°C for 1.5 hours, keep it at 210°C for 2 hours, keep it at 240°C for 2 hours, and keep it at 300°C for 1 hour, cool it, and obtain a soluble olefin polyimide.

[0034] Step S2, add 30g of soluble alkenyl polyimide to 600mL N,N-dimethylformamide, stir to dissolve, add 2.4g of polyisoprene, 100mL of toluene cosolvent, 12mg of azobisisobutyronitrile and 90mg of trimethylolpropane tris(thioglycolic acid), heat to 65°C, stir to react for 72h, pour the solution into methanol, filter and wash with ethanol to obtain polyisoprene grafted polyimide.

[0035] Step S3, adding 10kg natural rubber, 2kg polyisoprene grafted polyimide, 400g zinc oxide, 340g stearic acid, 77g accelerator tetramethylthiuram disulfide and 161g 2,2'-dibenzothiazole disulfide, 130g antioxidant N-cyclohexyl-N'-phenyl-p-phenylenediamine into a double-roll mill, mixing for 6min, then adding 140g sulfur, and after mixing, vulcanizing the obtained mixed rubber in a flat vulcanizer at 150°C for 20min, discharging, and obtaining a wear-resistant rubber composite material.

[0036] Example 6: Step S1, add 10mmol trifluoromethyldiamine monomer (prepared by Example 1) and 9.5mmol 4,4'-biphenyl ether dianhydride to N,N-dimethylformamide, stir and react at 20°C for 10h, then pour the solution into a mold, and place it in an oven for thermal imidization. The process is sequentially kept at 160°C for 1.5h, 200°C for 3h, 240°C for 2h, and 280°C for 1.5h, and then cooled to obtain a soluble olefin polyimide.

[0037] Step S2, add 30g of soluble alkenyl polyimide to 700mL N,N-dimethylformamide, stir to dissolve, add 4.8g of polyisoprene, 150mL of toluene cosolvent, 26mg of azobisisobutyronitrile and 190mg of pentaerythritol tetrakis-3-mercaptopropionate, heat to 80°C, stir to react for 48h, pour the solution into methanol, filter and wash with ethanol to obtain polyisoprene grafted polyimide.

[0038] Step S3, adding 10kg natural rubber, 3kg polyisoprene grafted polyimide, 400g zinc oxide, 400g stearic acid, 77g accelerator tetramethylthiuram disulfide and 183g N-cyclohexyl-2-benzothiazole sulfonamide, 148g antioxidant N-cyclohexyl-N'-phenyl-p-phenylenediamine into a double-roll mill, mixing for 6min, then adding 180g sulfur, and after mixing, vulcanizing the obtained mixed rubber in a flat vulcanizer at 150°C for 25min, discharging, and obtaining a wear-resistant rubber composite material.

[0039] Comparative Example 1: Step S1, add 10kg natural rubber, 400g zinc oxide, 360g stearic acid, 54g accelerator tetramethylthiuram disulfide and 146g N-cyclohexyl-2-benzothiazolesulfonamide, 130g antioxidant N-cyclohexyl-N'-phenyl-p-phenylenediamine into a double-roll mill, mix for 4min, then add 180g sulfur, and after mixing, vulcanize the obtained mixed rubber at 145°C in a flat vulcanizer for 30min, discharge, and obtain a wear-resistant rubber composite material.

[0040] Comparative Example 2: Step S1, add 10kg natural rubber, 500g soluble olefin polyimide (prepared by Example 3), 400g zinc oxide, 360g stearic acid, 54g accelerator tetramethylthiuram disulfide and 146g N-cyclohexyl-2-benzothiazole sulfonamide, 130g antioxidant N-cyclohexyl-N'-phenyl-p-phenylenediamine into a double-roll mill, mix for 4min, then add 180g sulfur, and after mixing, vulcanize the obtained mixed rubber at 145°C in a flat vulcanizer for 30min, discharge, and obtain a wear-resistant rubber composite material.

[0041] Comparative Example 3: Step S1, add 10mmol 4,4'-diaminostilbene dihydrochloride and 20mmol potassium carbonate to N,N-dimethylformamide, stir to neutralize the hydrochloric acid, then add 10mmol 4,4'-biphenyl ether dianhydride, stir and react at 25°C for 10h, then pour the solution into a mold, and place it in an oven for thermal imidization, the process is sequentially kept at 150°C for 2h, 200°C for 3h, 240°C for 1.5h, 300°C for 1h, and cooled to obtain olefin polyimide.

[0042] Step S2, add 30 g of alkenyl polyimide to 800 mL of N,N-dimethylformamide, stir and add 3.9 g of polyisoprene, 100 mL of toluene cosolvent, 17 mg of azobisisobutyronitrile and 130 mg of pentaerythritol tetrakis-3-mercaptopropionate, heat to 65 ° C, stir and react for 72 hours, pour the solution into methanol, filter and wash with ethanol to obtain polyisoprene grafted polyimide.

[0043] Step S3, adding 10kg natural rubber, 500g polyisoprene grafted polyimide, 400g zinc oxide, 360g stearic acid, 54g accelerator tetramethylthiuram disulfide and 146g N-cyclohexyl-2-benzothiazole sulfonamide, 130g antioxidant N-cyclohexyl-N'-phenyl-p-phenylenediamine into a double-roll mill, mixing for 4min, then adding 180g sulfur, and after mixing, vulcanizing the obtained mixed rubber in a flat vulcanizer at 145°C for 30min, discharging, and obtaining a wear-resistant rubber composite material.

[0044] The wear resistance is tested according to the method of GB / T 1689-2014. The tear strength of the wear-resistant rubber composite material is tested according to the method of GB / T 529-2009. The Shore A hardness is tested according to the method of GB / T 531.1-2008.

[0045] The wear-resistant rubber composite material was placed in a hot air aging tester at 200°C for 120 hours, and then tested for tear strength, Shore A hardness and wear resistance after cooling.

[0046] Table 1 Performance test of wear-resistant rubber composite materials

[0047] The Akron abrasion loss of the rubber composite material of Comparative Example 1 is large, the wear resistance is poor, and the tear strength and Shore A hardness are low, and the mechanical properties are poor. After the heat aging test, the Akron abrasion loss increases greatly, the tear strength and Shore A hardness decrease greatly, the mechanical properties deteriorate, and the heat resistance is poor.

[0048] Polyisoprene grafted polyimide is added to the wear-resistant rubber composite materials of Examples 3-6, and a large number of polyisoprene molecular chains are introduced into the side chains of polyimide, which significantly improves its compatibility with natural rubber, makes the polyimide evenly dispersed in the natural rubber matrix, plays a good reinforcement role, improves the tear strength and Shore A hardness of the rubber material, reduces the Akron abrasion, improves the mechanical properties and wear resistance of the natural rubber material, and the polyimide has a strong high temperature resistance and is evenly dispersed in the natural rubber matrix, which is beneficial to improve its heat resistance. After the heat aging test, the natural rubber material still has a low Akron abrasion and a high tear strength and Shore A hardness, and maintains good wear resistance and mechanical properties.

[0049] Compared with Example 1, the soluble olefinic polyimide added in Comparative Example 2 has no grafted polyisoprene molecular chain, resulting in poor compatibility with natural rubber and inability to be evenly dispersed in the rubber material matrix. The reinforcement effect is low, the Akron wear of the natural rubber material is large, and the tear strength and Shore A hardness are low.

[0050] Comparative Example 3 utilizes alkenyl polyimide with pentaerythritol tetrakis-3-mercaptopropionate and polyisoprene to graft polyimide for cross-linking grafting reaction. Since alkenyl polyimide does not contain trifluoromethyl, the solubility of polyimide in N,N-dimethylformamide is poor, and it is difficult to undergo grafting reaction with polyisoprene, resulting in difficulty in introducing a large number of polyisoprene molecular chains into the side chains of polyimide. The compatibility of polyimide with natural rubber is poor, and it is not well dispersed in the rubber material matrix, resulting in low reinforcement and repair effect. The natural rubber material has a large Akron abrasion loss, and low tear strength and Shore A hardness.

[0051] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing a wear-resistant rubber composite material, characterized in that: The preparation method comprises the following steps: Step S1, add 4,4'-biphenyl ether dianhydride, structural formula: trifluoromethyldiamine monomer, stirring for reaction for 6-10 hours, then pouring the solution into a mold, placing it in an oven, keeping it at 150-160°C for 1.5-2 hours, 200-210°C for 2-3 hours, 240-250°C for 1.5-2 hours, and 280-300°C for 1-1.5 hours, cooling, and obtaining a soluble olefin polyimide; Step S2, adding soluble alkenyl polyimide to N,N-dimethylformamide, stirring to dissolve, adding polyisoprene, toluene cosolvent, azobisisobutyronitrile and mercapto crosslinking agent, stirring to react, pouring the solution into methanol, filtering and washing with ethanol to obtain polyisoprene grafted polyimide; Step S3, adding 100 parts by weight of natural rubber, 5-30 parts of polyisoprene grafted polyimide, 4-5 parts of zinc oxide, 3.4-4.2 parts of stearic acid, 2-2.6 parts of accelerator, and 1.3-1.6 parts of antioxidant into a double-roll open mill, adding 1.4-1.8 parts of sulfur after mixing, and vulcanizing the obtained mixed rubber in a flat vulcanizer after mixing, discharging the material, and obtaining a wear-resistant rubber composite material.

2. The method for preparing the wear-resistant rubber composite material according to claim 1, characterized in that: In the step S1, the molar ratio of trifluoromethyldiamine monomer to 4,4'-biphenyl ether dianhydride is 100:(90-110).

3. The method for preparing the wear-resistant rubber composite material according to claim 1, characterized in that: In the step S2, the mass ratio of the soluble olefin polyimide, polyisoprene, azobisisobutyronitrile, and mercapto crosslinking agent is 100:(8-20):(0.04-0.1):(0.3-0.8).

4. The method for preparing the wear-resistant rubber composite material according to claim 1, characterized in that: The mercapto crosslinking agent is pentaerythritol tetrakis-3-mercaptopropionate or trimethylolpropane tris(thioglycolic acid).

5. The method for preparing the wear-resistant rubber composite material according to claim 1, characterized in that: The reaction temperature in step S2 is 65-80° C., and the reaction time is 48-72 hours.

6. The method for preparing the wear-resistant rubber composite material according to claim 1, characterized in that: In step S3, the accelerator is any one or a combination of tetramethylthiuram disulfide, 2,2'-dibenzothiazole disulfide, and N-cyclohexyl-2-benzothiazole sulfenamide; and the antioxidant is N-cyclohexyl-N'-phenyl-p-phenylenediamine.

7. The method for preparing the wear-resistant rubber composite material according to claim 1, characterized in that: The preparation method of the trifluoromethyldiamine monomer is: (1) Add 3-nitro-5-(trifluoromethyl)benzoic acid, 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride, and 1-hydroxybenzotriazole to N,N-dimethylformamide, and stir to activate for 60-90 minutes. Then, add 4,4'-diaminobenzene dihydrochloride and potassium carbonate, and stir to react for 12-18 hours. Add saturated sodium bicarbonate solution, filter, wash with water, and separate by silica gel column chromatography to obtain an intermediate; (2) Add the intermediate, Pd / C catalyst and hydrazine hydrate solution in a mass ratio of 100:(4.4-5.2):(60-74) to ethanol, heat to 70-80°C, condense and reflux for 18-24 hours, filter and rotary evaporate the filtrate, separate by silica gel column chromatography, and obtain trifluoromethyldiamine monomer.

8. The method for preparing the wear-resistant rubber composite material according to claim 7, characterized in that: The molar ratio of the 3-nitro-5-(trifluoromethyl)benzoic acid, 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride, 1-hydroxybenzotriazole, 4,4'-diaminobenzene dihydrochloride and potassium carbonate is (200-220): (210-230): (210-230): 100: (340-380).

Citation Information

Patent Citations

  • A kind of preparation method of high damping polyimide fiber reinforced composite material

    CN104231348B